2021
DOI: 10.1016/j.foodhyd.2021.106650
|View full text |Cite
|
Sign up to set email alerts
|

Biological protein precipitation: A green process for the extraction of cucumisin from melon (Cucumis melo L. inodorus) by-products

Abstract: Cucumisin (CUC) from industrial melon by-products was separated for the first time through biological precipitation using carrageenan (CRG). This approach could represent a cost-effective and environmentally friendly process for the industries, avoiding the use of expensive equipment and toxic salts or solvents, such as butanol and ethanol. In this study, biological precipitation of proteins from melon by-products using CRG was studied and compared with conventional precipitation with ammonium sulphate. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Also, a study revealed the presence of several biologically active phytocompounds in Cucumis melo extracts obtained with various solvent systems, demonstrating the fruit's cancer-inhibiting properties, and supporting the fruit's use in future research for the treatment of various diseases [50]. The fruit is used for its juice, with thermal sterilization techniques, such as high-temperature and short-time sterilization, commonly employed to increase safety and expiration life [51]. According to study results, the peels possess proteolytic (4.24 U/mg protein) and milk-clotting (6300 One Milk-Clotting Unit/mg protein) activities, with a milk-clotting activity/proteolytic activity ratio of 1485.…”
Section: Cucumis Melo Lmentioning
confidence: 95%
“…Also, a study revealed the presence of several biologically active phytocompounds in Cucumis melo extracts obtained with various solvent systems, demonstrating the fruit's cancer-inhibiting properties, and supporting the fruit's use in future research for the treatment of various diseases [50]. The fruit is used for its juice, with thermal sterilization techniques, such as high-temperature and short-time sterilization, commonly employed to increase safety and expiration life [51]. According to study results, the peels possess proteolytic (4.24 U/mg protein) and milk-clotting (6300 One Milk-Clotting Unit/mg protein) activities, with a milk-clotting activity/proteolytic activity ratio of 1485.…”
Section: Cucumis Melo Lmentioning
confidence: 95%
“…Following this subject matter, another research work was carried out for the extraction of a poorly explored enzyme from melon by-products (peels) called cucumisin with proteolytic and milk-clotting properties. The precipitation process was conducted by applying carrageenan at a lesser concentration (0.003-0.006% w/v, pH 3), obtaining better purification factors on proteolytic and milk-clotting activity (2.11-and 17.65-fold, respectively), when compared with the ammonium salt precipitation (1.60-and 2.06-fold, respectively) as well as a high recovery yield of enzymatic activity (60-80%) [62]. In summary, based on the good results and insights attributed by the application of polyelectrolyte precipitation and its favorable patent applications and developments as a measure of technological innovation, it could be suggested that this technique not only represents an eco-friendly extractive method but also a promising technology to generate new business lines and be transferred to pilot or industrial levels for the obtention of bioactive proteins with high market demands.…”
Section: Innovation On Protein Recovery By Polyelectrolyte Precipitat...mentioning
confidence: 99%
“…At present, the commonly used pretreatment methods include liquid‐liquid extraction, solid‐phase extraction, immunoaffinity extraction, and protein precipitation, etc. These pre‐treatment methods usually require a time‐consuming procedure, expensive reagents, poor reproducibility, and complicated operations [2–6]. Toxic reagents also have certain adverse effects on operators and the environment.…”
Section: Introductionmentioning
confidence: 99%